1976
DOI: 10.1111/j.1744-7348.1976.tb00573.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the use of Bacillus subtilis with conventional fungicides for the control of apple canker (Nectria galligend)

Abstract: S U M M A R YIn a factorialized field trial cells of B a d u s subtilis or phenylmercuric nitrate (PMN) were applied as sprays in autumn to manually defoliated apple trees, cv. Bramley's Seedling, artificially infected with Nectria galligena. Trees were additionally sprayed with dithianon at intervals in May and June or left unsprayed at this time. B. subtilis in conjunction with dithianon, and PMN with dithianon were equally effective in the control of canker over a 2-yr period. Dithianon alone gave some cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Bacillus subtilis isolates were antagonistic to N. ditissima in vitro, and control of leaf scar infections was achieved (Swinburne et al 1975;Swinburne 1973). However, in a two-year field study Swinburne & Brown (1976) found that the bacterium alone was not effective without additional applications of dithianon. Dithianon alone was less effective than in combination with B. subtilis.…”
Section: Figurementioning
confidence: 99%
“…Bacillus subtilis isolates were antagonistic to N. ditissima in vitro, and control of leaf scar infections was achieved (Swinburne et al 1975;Swinburne 1973). However, in a two-year field study Swinburne & Brown (1976) found that the bacterium alone was not effective without additional applications of dithianon. Dithianon alone was less effective than in combination with B. subtilis.…”
Section: Figurementioning
confidence: 99%
“…To that effect, field studies are in progress. Indeed, B. subtilis and other biological products have not provided wound protection) on susceptible cultivars Swinburne & Brown 1976).…”
Section: Commercial Spray Experiments 4 (Cse4)mentioning
confidence: 99%
“…Successful integrated use of chemical and biological agents has been reported for both, soilborne pathogens [21,22] and air-borne pathogens [23,24]. Our study shows the importance of in vitro studies in order to plan integrated approaches to control fungal pathogens.…”
Section: Resultsmentioning
confidence: 75%